2020
DOI: 10.1140/epjc/s10052-020-7647-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of generalized polytropic equation of state on charged anisotropic polytropes

Abstract: In this paper, generalized polytropic equation of state is used to get new classes of polytropic models from the solution of Einstein-Maxwell field equations for charged anisotropic fluid configuration. The models are developed for different values of polytropic index n = 1, 1 2 , 2. Masses and radii of eight different stars have been regained with the help of developed models. The speed of sound technique and graphical analysis of model parameters is used for the viability of developed models. The analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…It has been demonstrated that the presence of charge affects the rate of gravitational collapse, luminosities, stellar masses and other physical features. Some recent examples of charged static stars and their interesting properties are given in [1][2][3][4][5][6]. In radiating stars, the radial pressure at the stellar boundary is nonvanishing [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the presence of charge affects the rate of gravitational collapse, luminosities, stellar masses and other physical features. Some recent examples of charged static stars and their interesting properties are given in [1][2][3][4][5][6]. In radiating stars, the radial pressure at the stellar boundary is nonvanishing [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Pandya et al [103], Bhar et al [104] studied the static spherically symmetric relativistic anisotropic compact object considering the Tolman VII solution as one of the metric potentials. Mardan et al [203] has used polytropic EoS to generate solutions. New anisotropic models of a strange star admitting the Chaplygin equation of state was proposed by Bhar [206], Kumar et al [208], etc.…”
Section: Anisotropy and Its Effectmentioning
confidence: 99%
“…Solutions to the Einstein field equations admitting a polytropic equation of state are not common with physical viable solutions being a rarity. For recent works on anisotropic stellar modeling by employing polytropic EoS one can go through the papers [199][200][201][202][203]. We have enlisted some metrics in Table XI which have been used to study the anisotropic stellar modeling with polytropic EoS and discussed the solutions briefly.…”
Section: E Polytropic Equation Of Statementioning
confidence: 99%
See 1 more Smart Citation
“…They found exact solutions of field equations by taking different values of polytropic index n and analyzed some mathematical models which were found physically viable and well behaved. Mardan et al [29,30] established new classes of polytropic models using spherical symmetry and analyzed the mass and radius of different astronomical objects.…”
Section: Introductionmentioning
confidence: 99%